A GENDER COMPARATIVE STUDY AMONG COLLEGE STUDENTS’ ENTREPRENEURIAL INTENTION FOCUSING ON INDIVIDUALS’ KNOWLEDGE EXPLORATION AND EXPLOITATION ACTIVITIES - Nabila, Khaira; Pujani, Vera; Rivai, Harif Amali (Jurnal Riset Entrepreneurship, 2024)
The contributions of young entrepreneurs are essential to navigate the challenges of a rapidly changing industry. To encourage more young people to start businesses, it's important to understand what drives entrepreneurial intention. Gender might also play a role in this motivation. This study aims to compare entrepreneurial intentions between male and female students, focusing on their learning activities and knowledge exploration. The research population includes all registered Andalas University students who have completed the compulsory entrepreneurship course. The sample, chosen through convenience sampling, consists of 412 respondents selected based on their availability and ease of access. The usable questionnaires were processed using SmartPLS 4.1.0.6. Multigroup analysis is utilized to know the difference between male and female respondents. The findings show that increasing innovativeness and self-efficacy is key to enhancing students' knowledge exploration and exploitation. Innovativeness benefits all students, while self-efficacy boosts confidence and involvement. Agreeableness helps female students with exploration and both genders with exploitation. There are no significant gender differences in how innovativeness affects these activities, but self-efficacy and agreeableness show notable gender differences. This research emphasizes the need for customized entrepreneurship programs that address gender-specific needs, such as mentorship and access to resources, to boost entrepreneurial intentions for both male and female students. It also highlights the importance of promoting gender equality in these programs.